Modified Pechini Synthesis of Proton‐Conducting Ba(Ce, Ti)O3 and Comparative Studies of the Effects of Acceptors on its Structure, Stability, Sinterability, and Conductivity. Issue 4 (26th December 2013) - Chi, Xiaowei; Zhang, Jingchao; Wen, Zhaoyin; Liu, Yu; Wei, W.‐C.
<x xml:space="preserve">Abstract</x> The phase structure, chemical stability, sinterability, and electrical performance of the proton‐conducting Ba(Ce, Ti)O3 solid solution with a series of acceptors M (M = In, Y, Sm) synthesized by a modified Pechini method were systematically investigated. The substitution of cerium with titanium was proved as an effective way to improve the stability of BaCeO3. Especially for the BaCe0.95Ti0.05O3−δ sample doped with In, no change in the phase was found even after treatment in the atmosphere containing both CO2 and H2O at 700°C for 10 h. Thanks to the highly sinteractive powders with particle size of ~100 nm, dense ceramics were easily acquired. Moreover, compared with the undoped BaCe0.95Ti0.05O3 sample, In, Y, and Sm dopants further improved the sinterability of the solid solution. In particular, In played a role of sintering aid and led to the largest linear shrinkage of the ceramics. As to the electrical performance, the transport properties of the samples under various atmospheres were analyzed and compared. The impedance tests demonstrated the best electrical performance of the Y‐doped samples.